MENINGKATKAN INTENSI MENYUSUI DENGAN VIDEO ASI EKSKLUSIF - Ika Rizqi L; Mira Triharini; Retnayu Pradanie (Universitas Airlangga, 2014)
Breastfeeding is the optimal way of providing the best nutrition for development of infants’ health. Breastfeedingshould begin immediately after baby birth until 2 years and exclusively for 6 month. Exclusive breastfeeding in Surabayahave not been on national target 80% exclusive breastfeeding success, so it needs to be improved. This study was aimedto analyze exclusive breastfeeding video effect to the increase in mother’s intention to breastfeed in PuskesmasMulyorejo. This study used quasy experimental design and population was pregnant mothers in Puskesmas Mulyorejo.The sampling used purposive sampling technique, based on third trimester pregnant mother, used 20 mothers consist of10 woman as experiment group and 10 woman as control group. Data collected by Infant Feeding Intension (IFI) Scaleand analyzed by Wilcoxon signed rank test and Mann Whitney U test with significant value α ≤ 0,05. The resultstatistically showed there was effect of exclusive breastfeeding video to mother’s intention to breastfeed inPuskesmas Mulyorejo (p= 0,007), and there was different between experiment group and control group after being givenexclusive breastfeeding video (p= 0,012). In conclusion, exclusive breastfeeding video that contains information aboutexclusive breastfeeding, lactation management, and social support was significantly effective to improve themother’s intention to breastfeed. Future research can examine the influence of the major determining factors indetail and behavioral intentions mother to exclusive breastfeed after giving birth